2012
DOI: 10.1007/978-94-007-4786-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Extraction of Soluble Non-Starch Polysaccharides and Viscosity Determination of Aqueous Extracts from Wheat and Barley

Abstract: Cereal grains contain various amounts of non-starch polysaccharides (NSP), which are composed predominantly of arabinoxylans, b-glucans and cellulose. The detrimental effect of soluble NSP is mainly associated with the viscous nature of these polysaccharides and their physiological effects on the digestive medium. Our study had in view to investigate the influence of some extraction conditions on the viscosity of wheat and barley aqueous extracts. Water extract viscosities (WEV) appeared to be related to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The viscosity, biological, and physiochemical properties of these polysaccharides are oblige of their beneficial physiological effects in the small and large intestine. [38,72] Generally, cell walls of cereal grains (2-8%) contain arabinoxylans, (1, 3; 1, 4)-β-glucans, arabinogalactan, and pectins. [35,72,73] Whereas, literature revealed that among cereals, barley and oats are rich in mixed linked β-glucans, while wheat, rye, and triticale contain arabinoxylans (Pentosans).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity, biological, and physiochemical properties of these polysaccharides are oblige of their beneficial physiological effects in the small and large intestine. [38,72] Generally, cell walls of cereal grains (2-8%) contain arabinoxylans, (1, 3; 1, 4)-β-glucans, arabinogalactan, and pectins. [35,72,73] Whereas, literature revealed that among cereals, barley and oats are rich in mixed linked β-glucans, while wheat, rye, and triticale contain arabinoxylans (Pentosans).…”
mentioning
confidence: 99%
“…[38,72] Generally, cell walls of cereal grains (2-8%) contain arabinoxylans, (1, 3; 1, 4)-β-glucans, arabinogalactan, and pectins. [35,72,73] Whereas, literature revealed that among cereals, barley and oats are rich in mixed linked β-glucans, while wheat, rye, and triticale contain arabinoxylans (Pentosans). [74] They are not digested by human's small intestinal enzymes and so contribute to total dietary fiber intake.…”
mentioning
confidence: 99%
“…This viscosity reduction in all may results from the degradation of soluble nonstarch polysaccharides by endogenous enzymes (Lee & Ronalds, 1972). Both arabinoxylans and betaglucans are the main sources of the flour dispersion viscosity and cleavage of them by endogenous xylanases (Capriţa & Capriţa, 2012;Caprita et al, 2011), and beta-glucanases will reduce the viscosity (Lai, Slade, & Fincher, 1993). Soluble proteins and soluble starch may also contribute to the dispersions viscosity and their hydrolysis respectively by native proteolytic enzymes (Kawamura & Yonezawa, 1982) and beta-amylases (Hara-Nishimura & Nishimura, 1987) of flour would take part in viscosity reduction.…”
Section: Effect Of Enzyme On Flour Dispersion Viscositymentioning
confidence: 99%
“…Measurement of water extract viscosity in cereals is an indirect means of estimation of their soluble nonstarch polysaccharide content such as beta‐glucan (Caprita et al., 2011; Gamel et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PNAs ou também chamados de polímeros não amido, são os principais componentes da parede celular de várias plantas, frutas, vegetais, grãos e cereais (CAPRITA;CAPRITA;CRETESCU, 2013;CUMMINGS et al, 1997a). Segundo Bailey (1973) Os polissacarídeos não amiláceos presentes na banana madura podem ser considerados como compostos bioativos que podem ser extraídos ou purificados das bananas ainda em estágios avançados de maturação (ANDERSON et al, 2009;CUMMINGS et al, 1997b;SCOTT;DUNCAN;FLINT, 2008;SLAVIN;SLAVIN;GREEN, 2007).…”
Section: Polissacarídeos Não Amiláceos (Pnas)unclassified